COMPETENCE BASED COMPENSATION SYSTEM IN PT. ABC - Hibatullah, Fadhil Muhammad; Pritasari, Adita (Journal of Business and Management, 2017)
Abstract. PT. ABC is a company which construct and develop one of rail basis transportation in Jakarta. The aims of this research are to improve compensation system in PT. ABC which can satisfy, motivate and fair for the employees and to analyze as well as identify suitable employee's basic salary using job evaluation in PT. ABC. The methodology used in this research is quantitative and qualitative approach. This research collected primary and secondary data as well as processed the data through several steps including qualitative approach of interview and observation as well as quantitative approach of point method to calculate the basic salary. The result of this research is, competence based compensation system is suitable to be implemented in PT. ABC because the purpose of this system is match to solve the company's issues or problem. The purpose of the competence based compensation system is to satisfy, motivate and fair the employees through a clear indicator or level of measurement of basic salary, especially for experiences and competencies indicator. There is also the result of basic salary calculation by the researcherÂ Keywords: Competence-Based Compensation System, Job Analysis, Job Evaluation, Jakarta, Transportation Modes